Epigallocatechin-3-gallate Protects against Hydrogen Peroxide-Induced Inhibition of Osteogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells - Dawei Wang; Yonghui Wang; Shihong Xu; Fu Wang; Bomin Wang; Ke Han; Daqing Sun; Lianxin Li (Stem Cells International)
Oxidative stress induces bone loss and osteoporosis, and epigallocatechin-3-gallate (EGCG) may be used to combat these diseases due to its antioxidative property. Herein, oxidative stress in human bone marrow-derived mesenchymal stem cells (BM-MSCs) was induced by H2O2, resulting in an adverse effect on their osteogenic differentiation. However, this H2O2-induced adverse effect was nullified when the cells were treated with EGCG. In addition, treatment of BM-MSCs with EGCG alone also resulted in the enhancement of osteogenic differentiation of BM-MSCs. After EGCG treatment, expressions of β-catenin and cyclin D1 were upregulated, suggesting that the Wnt pathway was involved in the effects of EGCG on the osteogenic differentiation of BM-MSCs. This was also confirmed by the fact that the Wnt pathway inhibitor, Dickkopf-1 (DKK-1), can nullify the EGCG-induced enhancement effect on BM-MSC’s osteogenic differentiation. Hence, our results suggested that EGCG can reduce the effects of oxidative stress on Wnt pathway in osteogenic cells, which supported a potentially promising therapy of bone disorders induced by oxidative stress. Considering its positive effects on BM-MSCs, EGCG may also be beneficial for stem cell-based bone repair.